Home Quarantine Challenges and Psychological Status of Bangladeshi University Students during COVID-19 - Mizanur Rahman; Saidur Rahaman (Camarines Sur Polytechnic Colleges, 2021)
The study determined the home quarantine challenges and psychological status of Bangladeshi University students in the COVID-19 pandemic break-out. The study also looked into the impact of home quarantine challenges on the psychological status of the student. A well-structured questionnaire was created and circulated to respondents through various social media platforms and utilized the snowball sampling technique. A total of 250 graduate and undergraduate students were taken as respondents of this study. Statistical Packages for Social Science (SPSS) software was used to complete the data analysis procedure. The findings of the study show that the most noteworthy home quarantine challenges for Bangladeshi University students are the lack of awareness of home quarantine advantages (82%), insufficient financial support from their families (78%), and unsatisfactory medical support (77%). Also, home quarantine challenges are positively connected to psychological status (r=.364**) and it had a significant impact (β=.287, p<0.00) on psychological status in the pandemic period. The study also aided the policymakers in the better understanding of home quarantine challenges and the psychological status of Bangladeshi students. However, out of seven divisions in Bangladesh only students of Dhaka and Sylhet were selected to be the respondents. This caused difficulty in generalizing the findings of the study.